WKB Approximation in Noncommutative Gravity - Buric, M.; Madore, J.; Zoupanos, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We consider the quasi-commutative approximation to a noncommutative geometry defined as a generalization of the moving frame formalism. The relation which exists between noncommutativity and geometry is used to study the properties of the high-frequency waves on the flat background.